2017
DOI: 10.17116/hirurgia2017355-60
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in the lesions sizes and the incidence of complete epithelialization during the treatment of diabetic foot syndrome over a period of 4 weeks (multicenter study)

Abstract: Biomaterial Collost using in complex treatment of diabetic foot syndrome resulted in more rapid and effective healing of the ulcer. The treatment success increased from 43% to 72%. Complete epithelialization was achieved by 2.6 times more rapidly in conjunction with reduction the incidence of unsuccessful treatment results by 4.1 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…The positive effect of collagen that we have established experimentally confirms the clinical effectiveness of its use even in the treatment of chronic wounds. [15][16][17] This allows us to conclude about the unity of the mechanisms of collagen influence on acute and chronic wound regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effect of collagen that we have established experimentally confirms the clinical effectiveness of its use even in the treatment of chronic wounds. [15][16][17] This allows us to conclude about the unity of the mechanisms of collagen influence on acute and chronic wound regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…All selected injectables were of biological origin and derived from mammals; their effectiveness in wound treatment has been previously proven in clinical and experimental studies. These include collagen (Collost ® ; which contains native unreconstructed collagen obtained from the skin of cattle), [15][16][17][18][19] deproteinized calf blood hemoderivative (DCBH; Actovegin ® ), [20][21][22] and mesenchymal stem cells (SCs). [23][24][25][26][27][28] An obvious advantage of the injectable drugs is the ability to accurately administer a certain volume and dose of the drug to the same location in all animals, providing identical wound treatment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that the use of native collagen products does not produce side effects (58,59,63,64,68), which attests to high safety of this treatment.…”
Section: Use Of Native Collagen In the Treatment Of Diabetic Foot Synmentioning
confidence: 97%
“…Use of Collost led to a 1.8-fold reduction in time of wound preparation for autodermoplastic closure (32.0±4.6 days versus 56.8±8.7 days in the comparator group) (62). Preliminary results of a multicenter, randomized prospective clinical trial encompassing 71 patients with diabetic foot syndrome Wagner II -III showed that native collagen (Collost) effectively decreased the length, width, area and volume of diabetic ulcers so that epithelialization could occur faster (63,64). After 4 weeks of treatment, complete epithelialization was observed in 22.2% of patients from the main group (Collost) and in 8.6% of patients from the comparator group (standard therapy).…”
Section: Use Of Native Collagen In the Treatment Of Diabetic Foot Synmentioning
confidence: 99%
“…Как гелевая форма биоматериал Коллост активно используется в общехирургической практике для регенерации мягких тканей в лечении хронических ран, трофических язв, синдрома диабетической стопы. Проведенные исследования и аналитические обзоры показывают высокую эффективность коллагенового биоматериала в лечении хронических раневых дефектов различной этиологии [5][6][7][8][9].…”
Section: Clinical Estimation Of the Efficacy Mesenchymal Stem Cells Aunclassified